Sosialisasi Bahaya Penyalahgunaan Narkoba Untuk Meningkatkan Kesadaran Pelajar SMP Swasta PGRI 32 Pulau Kampai - Sufriansyah; Nurul Hasanah; Alfera Ridha; Fahrul Haji; Adinda Puja Lestari (Fusion: Jurnal Pengabdian kepada Masyarakat, 2023)
Drug abuse in Indonesia is increasing and the problems it causes are also increasingly complex. It is undeniable that drugabuse occurs a lot among adolescents which has a negative impact both physically, psychologically, socially andeconomically and so on. The dangers of this drug can also threaten the health and even the lives of people who use it. Thebehavior of some teenagers who have ignored the values, rules, norms and laws that apply in society is one of the triggers forthe rise of drug abuse among the younger generation. The purpose of this activity is to increase student awareness aboutdrug abuse for students. In this activity the population taken was all students of Private MTS PGRI 32 Kampai Island, but30 students were sampled in this activity. The results of community service activities show that people gain good and correctknowledge and understanding about the dangers of drug abuse, so that they can prevent and deal with drug abuse andillicit trafficking, especially among the younger generation.